Effect of Pomegranate Juice on Dextran Sulfate Sodium Salt-Induced Ulcerative Colitis in Mice - WU Shujuan, WANG Xinjun, ZHANG Wusheng, MENG Weihong, XIA Yucheng, ZHANG Runguang, ZHANG Youlin (Shipin Kexue, 2023)
Ulcerative colitis is a chronic inflammatory bowel disease with unclear pathogenesis and is difficult to cure. The incidence rate is increasing year by year, and there is high drug dependence for the treatment of ulcerative colitis, which leads to obvious the treatment resistance to s side effects. Therefore, seeking natural health products for nutritional therapy has become an attention focus of attention. In this articlestudy, dextran sulfate sodium salt (DSS) was used to establish a mouse model of ulcerative colitis. The mice were intervened with 5-aminosalicylic acid (5-ASA) (130 mg/(kg mb∙d)) or pomegranate juice (30% and 100%, 10 mL/d). Body mass, disease activity index (DAI) and colon length were measured, liver and kidney function and oxidative stress were measured by biochemical kits, the levels of inflammatory factors were measured by enzyme-linked immunosorbent assay (ELISA), colon tissue sections were observed, and the contents of fecal short-chain fatty acids (SCFAs) were determined by gas chromatography-mass spectrometry (GC-MS). Finally, a comprehensive evaluation of the effect and mechanism of pomegranate juice against ulcerative colitis in mice was exploredperformed. Compared with the DSS group, body mass and colon length in the pomegranate juice intervention group was increased, DAI was decreased, liver and kidney functions were improved, and could the expression of proinflammatory factors was significantly decreased (P < 0.01). In addition, anti-inflammatory factor expression was significantly enhanced (P < 0.01), reduce the level of oxidative stress and the activity of inflammatory marker myeloperoxidase (MPO) were significantly reduced (P < 0.01), the level of up-regulate fecal SCFAs was up-regulated, andimprove the colonic epithelial structure was improved. Pomegranate juice can attenuate intestinal mucosal damage and liver and kidney dysfunction, and has a good therapeutic effect on DSS-induced ulcerative colitis in mice.